A Homozygous TPO Gene Duplication (c.1184_1187dup4) Causes Congenital Hypothyroidism in Three Siblings Born to a Consanguineous Family - Cangul, Hakan; Aydin, Banu K.; Bas, Firdevs (Journal of Pediatric Genetics, 2015)
Congenital hypothyroidism (CH) is the most common neonatal endocrine disease, and germ-line mutations in the TPO gene cause the inherited form of the disease. Our aim in this study was to determine the genetic basis of congenital hypothyroidism in three affected children coming from a consanguineous Turkish family. Because CH is usually inherited in autosomal recessive manner in consanguineous/multicase families, we adopted a two-stage strategy of genetic linkage studies and targeted sequencing of the candidate genes. First, we investigated the potential genetic linkage of the family to any known CH locus, using microsatellite markers, and then screened for mutations in linked-gene by conventional sequencing. The family showed potential linkage to the TPO gene and we detected a homozygous duplication (c.1184_1187dup4) in all cases. The mutation segregated with disease status in the family. This study confirms the pathogenicity of the c.1184_1187dup4 mutation in the TPO gene and helps establish a genotype/phenotype correlation associated with this mutation. It also highlights the importance of molecular genetic studies in the definitive diagnosis and accurate classification of CH.
Keywords: TPO; mutation; genetics; duplication; congenital hypothyroidism; thyroid dyshormonogenesis